Flexural responses of hybrid steel-polyethylene fiber reinforced cement composites containing high volume fly ash - Ahmed, Shaikh; Maalej, M.; Paramasivam, P. (Elsevier, 2007)
Strain hardening and multiple cracking behavior of hybrid fiber reinforced cement composites containing different hybrid combinations of steel and polyethylene (PE) fibers under four-point bending are reported. The total volume fraction of fibers was kept constant at 2.5% to maintain a workable mix. Effects of increase in fly ash content as partial replacement of cement beyond 50%, such as 60% and 70% on the flexural response of hybrid steel-PVA (polyvinyl alcohol) and steel-PE fiber composites are also evaluated here. Among composites with different volume ratios of steel and PE fibers, the composite with 1.0% steel and 1.5% PE was found to show the highest flexural strength and that with 0.5% steel and 2.0% PE exhibited highest deflection and highest flexural toughness. Generally, the steel-PE hybrid composites exhibited lower flexural strength but higher deflection capacity than steel-PVA hybrid composites. The rate of strength loss after peak load in steel-PE hybrid composites was found low compared to steel-PVA hybrid system. The 50% replacement of cement by fly ash is found to be an optimum fly ash content in hybrid fiber composites.